The Banco Delta Asia affair: the USA patriot act and allegations of money laundering in Macau - Gaylord, Mark S. (Crime, law and social change, 2008)
The anti-money laundering laws of the US are the most powerful in the world. Their broad provisions and extra-territorial reach pose risks to financial institutions around the world. Although they are not widely understood, recent cases demonstrate how these laws operate. In this paper I briefly describe Macau, the new gambling capital of the world; analyze the alleged role of Banco Delta Asia (BDA), a small, family-owned bank in Macau, in money laundering on behalf of North Korea; and offer some observations on the controversial use of Section 311 of the USA Patriot Act.